Resolution of symptoms of rectal prolapse after repair of vaginal prolapse: A report of two cases - Gregory Vurture; Nina Jacobson (Elsevier, 2024)
Pelvic organ prolapse (POP) is a very common problem that can affect any aspect of the pelvic floor. Often, vaginal and rectal prolapse occur simultaneously. Prior case reports have suggested resolution of symptoms of rectal prolapse in those with concomitant rectal and vaginal prolapse; however, the overall body of evidence is limited. We present the cases of two patients who had complete resolution of their symptoms of rectal prolapse after repair of a concomitant vaginal prolapse. Both patients underwent a traditional rectocele repair and perineoplasty, and subsequently reported complete resolution of their symptoms of rectal prolapse, which persisted at their six-month post-operative visits. The second patient ultimately canceled a previously scheduled rectopexy with colorectal surgery. Perhaps a rectocele repair with perineoplasty is limiting rectal mobility, and therefore eliminating its ability to prolapse or intussuscept and cause bothersome symptoms. We suggest that those with concomitant vaginal and rectal prolapse desiring corrective surgery first undergo a less invasive vaginal repair. Post-operative re-evaluation of the symptoms rectal prolapse might then demonstrate that a more invasive rectal prolapse repair, which may involve a colon resection and prolonged hospital stay, was not in fact needed. Further prospective and randomized study is needed to determine the long-term outcomes of concomitant rectal and vaginal prolapse in those who first undergo a vaginal repair.